Cultivating Okra in Punjab - Verma, Arti; Pathania, Mandeep (Indian Horticulture, 2023)
Okra locally known as Bhindi is cultivated widely as a food crop in the tropical and subtropical regions across the globe. The pods of okra play an important role in human diet as they are rich in dietary fibre, proteins, amino acids especially lysine and tryptophan, carbohydrates, minerals, vitamins and antioxidants. Mucilage and fibre content present in okra helps in lowering down the glucose level and are good for diabetic patients. Okra is gaining importance with regards to its nutritional, medicinal, and industrial value. Apart from nutritional and health importance, okra plays an important role in income generation and subsistence among rural farmers in developing countries like India.